A comparative study of eschatology in Christianity and African traditional religion - Ekeke, Emeka Charles (Verbum et ecclesia, 2024)
The concept of eschatology remained a captivating theological subject that theologians dedicated substantial time and resources to comprehend. Contrary to popular belief, some Christians may not prioritise theological discussions about eschatological details. Eschatological discourse - the fate of the universe, including humans and the physical world - may also be prioritised. Death, the second coming of Christ, judgement, rewards, heaven and hell are some of the eschatological themes that fascinate and disturb people because of limited understanding about the afterlife. African tradition religion (ATR) has been criticised for omitting eschatology in its belief system which this study debunks. This study showed that Christianity and ATR have the concept of eschatology and identified the main points of convergence and divergence in their eschatologies to demonstrate that ATR’s eschatology is well-established but different from Christianity’s. This paper adopts theoretical research, often referred to as conceptual research, since it is aimed at advancing knowledge. Christianity and ATR agree that physical death ends life in the body, and death symbolises the afterlife. Earthlings have limited time to fulfil their duties. Both sides agree that the soul and spirit survive death and resurrection. Christianity and ATR share many beliefs and traditions across sects, ethnicities and regions. These factors influence the eschatology of each tradition. Both faiths agree that present decisions impact fate and eternity. They also agree that God opposes immorality, but the virtuous will inhabit a place of joy. Positive and negative conduct are punished differentially. Intradisciplinary and/interdisciplinary implications: This work discusses end-of-life issues that strongly relate to systematic theology and African traditional religion, emphasising that while their eschatologies differ, they share a belief in life after death. African traditional religion should not be mocked as a religion without eschatology.